THE TECHNOLOGICAL EVOLUTION OF FETAL MONITORING IN PREGNANCY CARE - Rodrigues, Cristiano Salles; Hasenclever, Lia; Shimoda, Eduardo (Journal Health and Technology - JHT, 2022)
The current context of medical activity demands from obstetricians a broad understanding of the scientific and technological advances. The objective of this article is to reveal the historical evolution of medical practices and technology in a particular field of health, namely the health of the fetus and the medical practices of its follow-up, in the face of the enormous technological advances that have occurred in the supply of cross-cutting technologies with potential use in this particular field. The methodology used was a non-systematic bibliographic review carried out in scientific journals in the medical field, and for the interpretation of the material collected, the approach of sectoral innovation system was adopted, which can be defined as a network of agents that interact in a specific technological field. The main results of the research show that over the centuries, with the advancement of technology, new equipment has been proposed to eliminate the limitations of interobserver interpretation, thus allowing new multicenter randomized studies. Furthermore, it has become clear that the health crisis caused by the Coronavirus limited, broke, and disrupted face-to-face care in all medical fields and served as a springboard for accelerating the use of electronic systems and artificial intelligence in medical care. And finally, it can be observed that the process of technological diffusion encounters several tensions between those who defend remote prenatal care and those who have aversion or distrust towards modernization, excessive medical conservatism, lack of regulation on the subject, and ethical issues that limit its advances.